Does trust mediate the relationship between entrepreneurial capacity and commitment? the perspective of the franchise industry in Malaysia - Mohd, Zalena; Mohd Ishan, Zahira (Primrose Hall Publishing Group, 2020)
The franchise industry is one of the most widely recognised business forms promising profitable business ownership. Inherent in the franchise business management is the unique relationship between the entrepreneurs in the franchise business, namely the franchisors and franchisees. It appears that trust is the key to the ongoing franchise relationship. Hence this research investigates whether trust mediates the relationship between entrepreneurial capacity and commitment in the franchise industry in Malaysia. This research developed a conceptual model by reviewing the commitment-trust theory and also conducting an extensive literature review. Samples were selected from franchisees who operate their franchise business around Klang Valley area. A total of 291 completed questionnaires were analysed using PLS-SEM. The results identify that relationship has a significant direct effect between entrepreneurial capacity and commitment. The findings also indicate that trust mediates the relationship between entrepreneurial capacity and commitment with partial mediation statistically significant at 0.01. This research’s results are likely to add on and contribute to the literature on the title above. The result also could be agreed by franchisors in defining the commitment amongst the franchisees that can become the prominent contender for the business of franchise. The author claims about this study that it would furnish a significant functional foundation for franchisors in the franchisees’ selection procedure.